2013
DOI: 10.3390/ani3010158
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological Survey of Plants Used in the Traditional Treatment of Gastrointestinal Pain, Inflammation and Diarrhea in Africa: Future Perspectives for Integration into Modern Medicine

Abstract: Simple SummaryThis review provides an inventory of numerous plant species used as traditional remedies for pain and diarrhea in Africa. Africa can emulate advances in traditional Chinese medicine through research, commercialization, teaching traditional medicine in medical schools, and incorporating botanical products in treating veterinary and human patients. Prioritized research of plant species with proven folklore in treating pain and diarrhea using high throughput screening to identify and test bioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 170 publications
1
31
0
1
Order By: Relevance
“…Species belonging to Leguminosae (Caesalpinioideae, Mimosoideae and Papilionoideae) and Rubiaceae families were the most commonly used in treatment of diseases in the study area. In the Sudanian zone, Leguminosae is an abundant family (Adomou et al, 2006) and it has often been reported as being the most important family in ethnopharmacological surveys all over the world (Stark et al, 2013).…”
Section: Medicinal Uses Of Tree Speciesmentioning
confidence: 99%
“…Species belonging to Leguminosae (Caesalpinioideae, Mimosoideae and Papilionoideae) and Rubiaceae families were the most commonly used in treatment of diseases in the study area. In the Sudanian zone, Leguminosae is an abundant family (Adomou et al, 2006) and it has often been reported as being the most important family in ethnopharmacological surveys all over the world (Stark et al, 2013).…”
Section: Medicinal Uses Of Tree Speciesmentioning
confidence: 99%
“…Natural plant secondary metabolites such as essential oils (EOs), tannins and saponins show promise as a means of reducing enteric methane from ruminants . However, the potential of extracts from West African plants to modify ruminal fermentation and to reduce enteric methane production has not been explored, despite a long history of use of these secondary metabolites in both human and veterinary medicine . Therefore, the purpose of this study was to investigate the potential of EOs from medicinal plants acclimated to Benin (West Africa) to modify in vitro rumen microbial fermentation and reduce methane production from Andropogon gayanus grass.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, inhibition of neutrophil hyper activation represents an interesting strategy to develop novel anti-inflammatory agents. There is increasing research in identifying novel natural plant products to integrate in conventional immunomodulators as they often have less side effects [11,12]. Our data showed that water-soluble polysaccharides extract isolated from medicinal plants, Anv inhibited fMLF-and PMA-induced superoxide anion (O 2 .-) production in human neutrophils.…”
Section: Discussionmentioning
confidence: 80%
“…To this end, bioactive products isolated from medicinal plant such as Garcinia buchananii and Ficus aurantiaca Griff have been shown to be antioxidative by respectively displaying in vitro H 2 O 2 scavenging activity [9] or inhibiting neutrophil ROS production [10]. Indeed, integration of the wealthy African medication for several diseases including inflammation in western medicine is considered as a promising challenge [11]. Medicinal plant extracts are usually made with water and water-soluble polysaccharides isolated from plants have attracted much attention because of their broad spectrum of therapeutic properties and relative low toxicity [12].…”
Section: Introductionmentioning
confidence: 99%